Augmenting Brand Trust: The Role of Decentralized Communities and Virtual Engagements in Web 3.0 Branding Strategies - Shah, Ami (Digital Repository of Theses, 2025)
This study explores how Web 3.0 branding strategies can contribute to building brand trust for the FMCG industry through decentralized communities, virtual engagements, and blockchain (BC) transparency. The aim was to check how decentralized communities affect, which virtual engagements are effective, which BC transparency contributes to, and how consumers perceive Web 3.0 interactions. The approach combined quantitative and qualitative techniques. A total of 328 participants were surveyed using structured questionnaires, and their responses were evaluated with the use of SPSS. Key analytical tools were descriptive statistics, regression analysis, correlation analysis, reliability (Cronbach's alpha), and frequency distribution. The findings revealed that brand trust was highly improved in a decentralized community, virtual engagements led to a positive consumer confidence, and BC transparency played a huge role in trust building. Moreover, consumer perceived value of Web 3.0 engagement also positively influenced the brand trust. The findings show that “fast-moving consumer goods” (FMCG) firms may strengthen customer loyalty and trust by strategically utilizing Web 3.0 technologies, which will lead to their success in the digital space in the long run.